A genetic variant near GATA3 implicated in inherited susceptibility and etiology of benign prostatic hyperplasia (BPH) and lower urinary tract symptoms (LUTS). Issue 11 (28th June 2017) - Na, Rong; Helfand, Brian T.; Chen, Haitao; Conran, Carly A.; Crawford, Susan E.; Hayward, Simon W.; Tammela, Teuvo L.J.; Hoffman‐Bolton, Judy; Zheng, Siqun L.; Walsh, Patrick C.; Schleutker, Johanna; Platz, Elizabeth A.; et al.
Abstract : Background: Benign prostatic hyperplasia (BPH) and associated lower urinary tract symptoms (LUTS) are common conditions. Little is known about their etiologies except that studies have suggested a substantial heritable component. Our objective is to provide a comprehensive, genome‐wide evaluation of inherited risks and possible mechanisms of etiology in BPH. Methods: We performed a three‐stage, genome‐wide association study (GWAS) of men from three independent populations, the REduction by DUtasteride of prostate Cancer Events (REDUCE) trial, the CLUE II cohort, and a Finnish hospital‐based population. DNA samples were genotyped using the Illumina HumanOmniExpress BeadChip in REDUCE and CLUE II, and using the Sequenom iPLEX system for the confirmation stage in the Finnish population. A logistic regression model was used to evaluate the association between each SNP and BPH/LUTS. Results: Fourteen SNPs reached P  < 5.0 × 10 −4 in the meta‐analysis of the two GWASs (CLUE II and REDUCE). A total of 773 SNPs were chosen for the confirmation step in the Finish cohort. Only one SNP (rs17144046) located ∼489 kb downstream of GATA3 remained significant after correction for multiple testing ( P  < 6.5 × 10 −5 ). This SNP marginally reached the GWAS significance level after performing a meta‐analysis of the three stages ( P‐meta  = 8.89 × 10 −7 ). Expression quantitative trait loci (eQTL) analyses showed that the risk allele (G) of rs17144046 was significantly associated with increased expression of GATA3 ( P  = 0.017). Reported studies indicated a close correlation between GATA3 and BPH pathogenesis and progression. Conclusions: Rs17144046 located near GATA3 was significantly associated with BPH/LUTS in three independent populations, but did not reach a stringent GWAS significance level. Genetic variants of GATA3 may play a role in the inherited susceptibility and etiology of BPH/LUTS. Further research in this area is needed.